Phylogeographic structure of the chloroplast DNA gene pool in North American Boechera: agenus and continental-wide perspective - Kiefer, Christiane; Dobeš, Christoph; Sharbel, Timothy Francis; Koch, Marcus (Molecular phylogenetics and evolution, 2009)
Continental-wide phylogeographic studies of plants in North America are rare. In our study we examined the phylogeographic history of Boechera (Brassicaceae) on a continental-wide scale testing if it is possible to do an analysis for 57 of the currently accepted taxa simultaneously. A large amount of haplotype sharing is explained both by recurrent hybridization and by non-differentiation of haplotypes since speciation. Hence, the chloroplast gene pool in Boechera predates speciation and therefore justifies the simultaneous analysis of a large number of taxa. Unrelated from taxon identity we can show that the evolutionary lineages detected have a different phylogeographic history in terms of glacial refugia and recently recolonised areas.